Experimental Study on Individual Taxpayer: Motivational Posture and Peer Reporting Behavior - Puspitasari, Elen; Susilowati, Yeye; Meiranto, Wahyu (JDM (Jurnal Dinamika Manajemen), 2017)
the effect of motivational postures and tax reporting behavior of one’s peers on taxpayer com-pliance was examined in this experimental study. This experimental research was conducted under the circumstances arranged and direct manipulation on taxpayer external factor, namely the independent variable is peer reporting behavior, so it can be determined causality effect of the independent variable on the dependent. The respondent is 81 taxpayers whose run the small business. A motivational posture was measured by using 29 statements developed by Braithwaite. Analysis of Covariance is used because this research conducting Quasi Experimen-tal Design Between-Subject with Covariate with random assignment method. Peer reporting behavior as an experimental variable consists of two level treatments. The result shows that the posture of motivation Indonesian taxpayers’ as a concomitant factor does not affect tax compli-ance decisions. Furthermore, this study provides evidence that peer reporting behavior were significant factors in explaining the experimental reporting decision. The findings of this study are expected to provide discourse to the government to improve tax compliance decisions in Indonesia in terms of posture motivation and peer reporting behavior among taxpayers.